2019
DOI: 10.1016/j.neuroimage.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of cortical folding waves and prematurity-related deviations revealed by spatial and spectral analysis of gyrification

Abstract: In the human brain, the appearance of cortical sulci is a complex process that takes place mostly during the second half of pregnancy, with a relatively stable temporal sequence across individuals. Since deviant gyrification patterns have been observed in many neurodevelopmental disorders, mapping cortical development in vivo from the early stages on is an essential step to uncover new markers for diagnosis or prognosis. Recently this has been made possible by MRI combined with post-processing tools, but the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 59 publications
2
53
0
Order By: Relevance
“…For each cluster on both hemispheres, we showed its growth trend and growth rate (per week) of surface area. To determine which function can more accurately model the growth trends that reflect the relationship between surface area and gestational weeks, we have used three previously‐adopted models, that is, a quadratic function (Clouchoux, Du Plessis, et al, ), a Gompertz function (Dubois et al, ; Wright et al, ), and a linear function (Garcia et al, ), to fit the growth trend in each cluster. From Table , we found that overall the quadratic function was best to fit the growth trends (with highest R 2 values) during 26–29 GW.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For each cluster on both hemispheres, we showed its growth trend and growth rate (per week) of surface area. To determine which function can more accurately model the growth trends that reflect the relationship between surface area and gestational weeks, we have used three previously‐adopted models, that is, a quadratic function (Clouchoux, Du Plessis, et al, ), a Gompertz function (Dubois et al, ; Wright et al, ), and a linear function (Garcia et al, ), to fit the growth trend in each cluster. From Table , we found that overall the quadratic function was best to fit the growth trends (with highest R 2 values) during 26–29 GW.…”
Section: Resultsmentioning
confidence: 99%
“…For large temporal intervals during fetal brain development with potential nonlinear growth patterns (Clouchoux, Du Plessis, et al, ; Dubois et al, ), the Pearson's correlation coefficient might not be the best method for measuring similarity, although some researchers have used the linear function to model the development trajectories of fetal cortical surface (Garcia et al, ). In this case, researchers can instead use other measures, for example, the Spearman's rank correlation coefficient, which can measure nonlinear correlations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations